О количественном учете некоторых амфибий на местах размножения в Приморском крае - Коротков, Ю.М. (Вестник зоологии, 1973)
To calculate amphibian males the Martof modified method (Martof, 1953) was applied. In the upper reaches of the river Suputinka (the Suputinian' reservation) 1928 males of Rana semiplicala Nikolsky were registered in cedar-broad-leaved forest in the area 240 m2. Near the river Tumangan in reed meadow (in the area I ha) 504 males of R. nigromaculata Hallowell and 51 males of Hyla japonica (G u n t h e r) were registered.